A comprehensive study on the occurrence rate and morphology characteristics of the acanthocephalan parasite in Javan spitting cobra (Naja sputatrix) in Sidoarjo, Indonesia - RYANKA EDILA; MUSTOFA HELMI EFFENDI; LUCIA TRI SUWANTI; HYUCK-KEUN KWON; ADITYA YUDHANA; APRIL HARI WARDHANA; ANISA ALHADA (Society for Indonesian Biodiversity, 2024)
Abstract. Edila R, Effendi MH, Suwanti LT, Kwon H-K, Yudhana A, Wardhana AH, Alhada A. 2024. A comprehensive study on the occurrence rate and morphology characteristics of the acanthocephalan parasite in Javan spitting cobra (Naja sputatrix) in Sidoarjo, Indonesia. Biodiversitas 25: 516-521. Javan spitting cobra (Naja sputatrix) are increasingly popular as pets worldwide and are often consumed by several communities in Indonesia. This trend needs attention from a public health perspective because it can potentially cause zoonotic diseases, including parasitic diseases. There is no comprehensive report on the prevalence of acanthocephalan parasite infection in Naja sputatrix. Therefore, this study aimed to estimate the prevalence rate of acanthocephalan infection and provide a detailed description of the morphology and morphometry in N. sputatrix from Indonesia. Ethical approval was obtained, and a total of 51 living wild-caught Javan spitting cobra was collected from local sellers. All samples were euthanized and observed for the presence of acanthocephalan. The total prevalence was recorded at 47.05%. A total of 56 acanthocephalans were collected, which were divided into 11 (19.6%) infecting muscles, 28 (50%) in viscera, and 17 (30.3%) located in subcutaneous tissues. The body length and diameter were 25-41 mm and 1.31-1.5 mm, respectively, with a proboscis diameter of 0.61-0.74 mm with 3 anterior hooks and 5-6 posterior rootless spines. This study represents the first detailed exploration of acanthocephalan's prevalence, morphological features, and morphometry in snakes in Indonesia.